2021
DOI: 10.1088/1755-1315/653/1/012117
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ perceptions of soil block nursery techniques on shallot seeds in Grobogan District, Central Java

Abstract: The research aimed to know the performance of seedlings and farmers’ perceptions of Shallot seed nursery techniques using soil blocks. The study was conducted in Grobogan Regency from September - November 2018. The research method used three nursery techniques, namely a seedbed with soil block, plastic bags, and plumbing. The data collected included technical data, namely data on the growth and productivity of shallots, and data on farmers’ perceptions of nursery techniques obtained by interviewing 30 farmers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Radar chart is a graphical method for displaying multivariate data consisting of three or more quantitative variables and presented in a two-dimensional chart starting at the same axis point [14]. Chanifah et al [15], farmers' attitudes before and after the dissemination process were categorized into three interval scales and were tested for significance using the Paired Sample T-test. The determination of the interval scale category is as follows: Average score = Total score/number of respondents Interval scale = (highest scorelowest score)/number of interval scales The three categories of farmer attitudes on an interval scale are as follows: a) Scale 1.00 -1.67 = Negative category, meaning that the farmers reject disseminated technology innovations and refuse to adopt b) Scale 1.68 -2.33 = Normal category, meaning that the farmers are ordinary or indifferent to the disseminated technology innovations c) Scale 2.34 -3.00 = Positive category, meaning that the farmers accept disseminated innovations and are ready to adopt The proportion of farmers' formal education is primary school 57.14%, junior high school 14.29%, senior high school 22.86%, and undergraduate 5.71%.…”
Section: Methods Of the Study Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…Radar chart is a graphical method for displaying multivariate data consisting of three or more quantitative variables and presented in a two-dimensional chart starting at the same axis point [14]. Chanifah et al [15], farmers' attitudes before and after the dissemination process were categorized into three interval scales and were tested for significance using the Paired Sample T-test. The determination of the interval scale category is as follows: Average score = Total score/number of respondents Interval scale = (highest scorelowest score)/number of interval scales The three categories of farmer attitudes on an interval scale are as follows: a) Scale 1.00 -1.67 = Negative category, meaning that the farmers reject disseminated technology innovations and refuse to adopt b) Scale 1.68 -2.33 = Normal category, meaning that the farmers are ordinary or indifferent to the disseminated technology innovations c) Scale 2.34 -3.00 = Positive category, meaning that the farmers accept disseminated innovations and are ready to adopt The proportion of farmers' formal education is primary school 57.14%, junior high school 14.29%, senior high school 22.86%, and undergraduate 5.71%.…”
Section: Methods Of the Study Implementationmentioning
confidence: 99%
“…Web of Conferences 361, 03010 (2022) https://doi.org/10.1051/e3sconf/202236103010 IConARD 2022technological innovation[15,16]. Table1shows the socio-economic characteristics of the respondent.The age of farmers ranged from 27-82 years old, with an average of 48.54 years.…”
mentioning
confidence: 99%
“…TSS germination can be improved by immersing the seed in gibberellin before sowing [33]. Meanwhile, another research of three nursery systems: soil block, plastic bag, and pullout system resulted in 60% average seed viability, with leaves first appearing five days after planting [34].…”
Section: B Agronomic Performancesmentioning
confidence: 99%
“…Research [35] also concluded that the seedling nursery system of TSS seed sown directly on media made from rice husk fuel + fertilizer (1:4) resulted in good seedling growth and health. The soil block nursery technique is an alternative to increase shallot production [34].…”
Section: B Agronomic Performancesmentioning
confidence: 99%
See 1 more Smart Citation